The climate change challenge and fiscal instruments and policies in the EU - Aris Avgousti; Francesco Caprioli; Giacomo Caracciolo; Marion Cochard; Pietro Dallari; Mar Delgado-Téllez; Jo\~ao Domingues; Marien Ferdinandusse; Daniela Filip; Carolin Nerlich; Doris Prammer; Katja Schmidt; et al. (European Central Bank (ECB), 2023)
Fiscal policy plays a prominent role in climate change mitigation and adaptation. An optimal combination of revenue policies, in particular taxes, and expenditure policies, such as subsidies and investment, is essential in order to achieve greenhouse gas emissions targets. This paper analyses the main fiscal instruments in place in European Union Member States, focusing on specific issues, such as the fiscal impact of extreme weather events, the interaction between debt sustainability and climate change, the green investment gap and the distributional impact of climate policies. The paper aims to provide an overview of existing fiscal policies and of the main fiscal challenges for a comprehensive European climate change strategy.
Keywords: H2; H5; H6; Q54; Q58; D63; 330; climate change; carbon tax; debt sustainability; green investment; extreme weather events; redistribution